Current Progress in Adipose Tissue Biology: Implications in Obesity and Its Comorbidities - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Obesity has been decades become a highly interest study, accompanied by the realization that adipose tissue (AT) plays a major role in the regulation of metabolic function.CONTENT: In past few years, adipocytes classification, development, and differentiation has been significant changes. The white adipose tissue (WAT) can transform to a phenotype like brown adipose (BAT) type and function. Exercise and cold induction were the most common factor for fat browning; however batokines such as fibroblast growth factor (FGF)-21, interleukin (IL)-6, Slit homolog 2 protein (SLIT2)-C, and Meteorin-like protein (METRNL) perform a beneficial browning action by increasing peroxisome proliferator-activated receptor gamma coactivator (PGC)-1α protein levels, a key factor to stimulate mitochondrial biogenesis and uncoupling Protein 1 (UCP1) transcription, thus change the WAT phenotype into beige.SUMMARY: AT recently known as a complex organ, not only bearing a storage function but as well as the master regulator of energy balance and nutritional homeostasis; brown and beige fat express constitutively high levels of thermogenic genes and raise our expectation on new strategies for fighting obesity and metabolic disorders.KEYWORDS: obesity, white adipose tissue, brown adipose tissue, beige adipose tissue, inflammation, IR, metabolic disease